2019
DOI: 10.3389/fnagi.2019.00178
|View full text |Cite
|
Sign up to set email alerts
|

Pioglitazone Reduces β Amyloid Levels via Inhibition of PPARγ Phosphorylation in a Neuronal Model of Alzheimer’s Disease

Abstract: It has been demonstrated that peroxisome proliferator-activated receptor γ (PPARγ) can regulate the transcription of its target gene, insulin-degrading enzyme ( IDE ), and thus enhance the expression of the IDE protein. The protein can degrade β amyloid (Aβ), a core pathological product of Alzheimer’s disease (AD). PPARγ can also regulate the transcription of other target gene, β-amyloid cleavage enzyme 1 ( BACE1 ), and thus inhibit the expression of the BACE1 prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 67 publications
(83 reference statements)
0
42
0
3
Order By: Relevance
“…recently, a study demonstrated that pioglitazone inhibits the phosphorylation of PParγ at Ser273 in vitro by inhibiting cdK5 expression, which in turn affected the expression of PParγ target genes Ide and Bace1, thereby promoting aβ degradation and reducing aβ production. This reduced aβ levels in the brain, thereby exerting neuroprotective effects in an AD model (53). These findings indicate that TZds have neuroprotective effects against ad.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…recently, a study demonstrated that pioglitazone inhibits the phosphorylation of PParγ at Ser273 in vitro by inhibiting cdK5 expression, which in turn affected the expression of PParγ target genes Ide and Bace1, thereby promoting aβ degradation and reducing aβ production. This reduced aβ levels in the brain, thereby exerting neuroprotective effects in an AD model (53). These findings indicate that TZds have neuroprotective effects against ad.…”
Section: Discussionmentioning
confidence: 78%
“…In the study, no experiments such as chromatin immunoprecipitation RT-qPCR, were performed to confirm whether CDK5 directly regulates PPARγ. However, our previous study reported that CDK5 regulates PPARγ ( 21 ), and performed co-immunoprecipitation experiments to confirm that Aβ promotes the binding of CDK5 to PPARγ ( 53 ). In addition, our previous study demonstrated that the PPARγ agonist pioglitazone inhibits PPARγ phosphorylation by inhibiting CDK5 expression, thereby promoting Aβ degradation and reducing Aβ production ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pioglitazone down-regulated CDK5 expression and PPARγ phosphorylation, and increased PPARγ expression, inhibiting BACE1 expression and Aβ production. The PPARγ antagonist GW9662 blocked these pioglitazone effects ( Quan et al, 2019b ), affirming they were mediated by the PPARγ receptor.…”
Section: Pparγ and Ad-related Risk Factorsmentioning
confidence: 90%
“…In both cell-based and in vivo models, PPARγ, but not PPARα or PPARδ ( Camacho et al, 2004 ), blocked the generation and release of Aβ peptides ( Sastre et al, 2003 , 2006 ; Liu et al, 2013 ; Gad et al, 2016 ; Quan et al, 2019b ) by blocking BACE1 mRNA and protein expression, and promoting Aβ peptide clearance ( Camacho et al, 2004 ). In vivo , PPARγ activation resulted in significantly reduced β-amyloid plaques ( Heneka et al, 2005 ; Escribano et al, 2010 ; O’Reilly and Lynch, 2012 ; Searcy et al, 2012 ; Liu et al, 2013 ; Quan et al, 2019b ). In vitro , the RXR ligand cis -retinoic acid alone was as effective as PPARγ agonists alone, including pioglitazone ( Camacho et al, 2004 ).…”
Section: Pparγ and Ad-related Risk Factorsmentioning
confidence: 99%
“…In recent years, PG has been used to improve some brain disorders. However, little is known about its neurotoxicity [10][11][12].…”
Section: Introductionmentioning
confidence: 99%